Specification of a Model for the Study of Reproductive Choice - Arger Verstapp Bund (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The discussion and specification of a model for the study of freedom of choice with respect to the termination of pregnancy was the objective of this document. A documentary study was carried out with an intentional selection of sources indexed to Dialnet, Latindex, Publindex, Redalyc and Scielo from 1961 to 2019, although the research design limited the results to the literature consulted, suggesting the extension of the work based on the information published in Copernicus, Ebsco, Scopus and WoS